Special Economic Zones and local economic activities in Ethiopia - Matthew Amalitinga Abagna (University College Dublin, UCD School of Economics, 2023)
Do Special Economic Zones (SEZs) increase local economic activities in developing countries? This paper explores this question by examining the aggregate district economic effects of SEZs, a place-based development policy in Ethiopia. The study relies on time and district variation in the establishment of SEZs to evaluate the within-district changes in nighttime light, a proxy for district economic activities. The Difference-in-Difference estimates show an increase in the average nighttime light of SEZs districts after the SEZs became operational. The effect varies with the SEZs type. SEZs with bigger land sizes and SEZs that operate in sectors other than textiles, garment and the leather industry tend to generate more economic activities in the SEZs districts. The impact is also positive and significant for publicly managed SEZs relative to privately managed SEZs. The study further explores whether SEZs generate spillover effects on the economic activities of districts bordering the SEZs districts. Overall, there is no consistent evidence that the policy has any significant effect on the economic activities of the SEZs commuting districts.
Keywords: F13; O25; O38; O55; R11; 330; Special Economic Zones; Economic Activities; Nighttime light; Ethiopia; Sub-Saharan Africa